A visual object-relationship query language for user-database interaction - SIAU, Keng (Institutional Knowledge at Singapore Management University, 1998)
User–database interaction has a direct and immediate effect on the effectiveness and efficiency of database end users. Traditional query languages like SQL and QBE require end users to understand the underlying data structure in the database. This is a burden on end users, especially novice end users who have little technical knowledge or understanding of database. To alleviate the need for end users to know the logical database organization, this paper proposes the use of an object–relationship (OR) model and a formal high-level visual query language as the interface. Using this interface, end users communicate only domain knowledge with the system without the need to specify the storage structure or search strategies. The end users deal only with the conceptual model of the database and not the actual physical implementation of the database. To demonstrate the expressive power of the visual query language, this paper also provides a proof to show that it is relationally complete and hence is as powerful as traditional languages such as SQL.